PENGETAHUAN JURU PARKIR TERHADAP PENYELENGGARAAN PELAYANAN PERPARKIRAN DI JL. H.R SOEBRANTAS KOTA PEKANBARU - Ebed Prawinata Lumbantobing; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT This research was conducted on Jalan Soebrantas. The purpose of this study is to find out knowledge of parking attendants about parking that applies in accordance with the provisions and find out the quality of service provided by parking attendants on Jalan HR. Soebrantas Pekanbaru City. The technique of determining the sample is Saturated Sampling and determines the number of samples of 85 people. The author uses a quantitative descriptive method and data instruments are observation and interviews. The results found by researchers of knowledge of parking attendants along Jl. H.R Soebrantas Pekanbaru city can be said to be good and the service for parking attendants along Jl. H.R Soebrantas Pekanbaru city can be said to be good Keywords: Parking attendant, level of knowledge, Quality of Service